Medición del nivel de satisfacción de los clientes externos de la empresa, “Satel Tv”, ubicada en la ciudad de Francisco de Orellana, cantón Joya de los Sachas, provincia de Orellana, para el año 2017 - Paucar Miñarcaja, Slendy Gabriela (2017)
The present work denominated “MEASUREMENT OF THE SATISFACTION LEVEL OF THE EXTERNAL CUSTOMERS OF THE COMPANY, "SATEL TV", LOCATED IN THE CITY OF FRANCISCO DE ORELLANA, CANTÓN JOYA DE LOS SACHAS, PROVINCE OF ORELLANA, FOR THE YEAR 2017”. has determined that between the client and the company runs a very important life cycle. In order to develop the present investigation and to measure customer perceived satisfaction, the main objective has been to carefully analyze each one of its study processes and to propose improvements for an adequate level of customer satisfaction, it was necessary to apply some methods and techniques with the In order for the research to have key foundations for sustaining this study, it was necessary to apply indicators to adequately analyze whether clients were feeling satisfied with the service they receive from the company, with the sole purpose of making the client feel like most important person, within this research has been used techniques such as the interview, which gives more emphasis on research and is the starting point for development, the survey allowed me to deepen one of each of its problems that the user has in front of the service he receives from the company, from such a man was that these are the events that the research carried out on the customers of the cable television company and that allows us to determine factors that help the process that has been evaluated in order to propose improvements for customer satisfaction. Finally, with all the data collected, we draw conclusions of progress and establish an Improvement Plan for each of the different areas of the company. The processes of satisfaction measurement and treatment of complaints detect areas of improvement that properly managed, contribute to increasingly achieve customer loyalty.